2016
DOI: 10.1126/sciadv.1600183
|View full text |Cite
|
Sign up to set email alerts
|

Not spreading in reverse: The dewetting of a liquid film into a single drop

Abstract: Dewetting films are not the time reversal of spreading droplets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 40 publications
(45 reference statements)
3
83
0
Order By: Relevance
“…5a; Supplementary Movie 11). This striking symmetry breaking is in stark contrast with the known isotropic dewetting of passive fluids [45][46][47] . Although pinning of the contact line [46][47][48] may contribute to breaking the radius island that loses its circular symmetry during dewetting, as shown by its contour (red line).…”
Section: Active Forces Govern Tissue Morphology During Dewettingmentioning
confidence: 60%
“…5a; Supplementary Movie 11). This striking symmetry breaking is in stark contrast with the known isotropic dewetting of passive fluids [45][46][47] . Although pinning of the contact line [46][47][48] may contribute to breaking the radius island that loses its circular symmetry during dewetting, as shown by its contour (red line).…”
Section: Active Forces Govern Tissue Morphology During Dewettingmentioning
confidence: 60%
“…Edwards et al (16) analyzed the dewetting of a liquid film into a single drop. For a large thin liquid film, they identified two dynamic regimes: A first regime where the radius decreases linearly in time, accompanied by an annular rim close to the contact line, and a second regime where the rim merges, and the film relaxes exponentially to a spherical cap shape.…”
Section: Aggregate Formation Dynamics Of Progenitor Cells Are Consistmentioning
confidence: 99%
“…2(a). For this regime, Edwards et al(16) found an analytical expression, relating the exponential relaxation time τ to the viscosity η a , the surface tension γ a and the volume V a of the aggregate, namely…”
mentioning
confidence: 99%
“…This modification is proven valid for different insulating layer thicknesses [86] opening a feasibility to applied dielectrowetting phenomenon into applications such as dynamically controlling droplets spreading [87] and retracting [88] (Fig. 2.21).…”
Section: Fundamentals Of Dielectrowetting and Its Applicationsmentioning
confidence: 90%
“…(H) Schematic of the dynamic contact angle versus time of the dewetting droplet. All the figures here are reproduced from the work of Edwards et al[88]…”
mentioning
confidence: 99%